Selaginella coriaceifolia (sect. Heterostachys; Selaginellaceae), a new lycophyte species from central Vietnam - Ye, Zi-Yu; Lu, Ngan Thi; Zhang, Liang; Zhou, Xin-Mao; Zhang, Li-Bing (Phytotaxa, 2020)
A new species, Selaginella coriaceifolia, is described and illustrated from central Vietnam. The new species can be distinguished from other species in Asia by its habit epilithic, main stem nearly isotomously branched, leaves strongly leathery, ventral leaves imbricate on stem and branch, dorsal leaves with reflexed arista at apex, and sporophylls nearly monomorphic. Molecular and morphological studies of the new species and its allies in S. subg. Heterostachys Baker sect. Heterostachys (Baker) Li Bing Zhang & X.M.Zhou are conducted.